Blue Light Switchable Cell–Cell Interactions Provide Reversible and Spatiotemporal Control Towards Bottom‐Up Tissue Engineering. Issue 4 (18th January 2019) - Yüz, Simge G.; Rasoulinejad, Samaneh; Mueller, Marc; Wegner, Anatol E.; Wegner, Seraphine V.
Abstract: Controlling cell–cell interactions is central for understanding key cellular processes and bottom‐up tissue assembly from single cells. The challenge is to control cell–cell interactions dynamically and reversibly with high spatiotemporal precision noninvasively and sustainably. In this study, cell–cell interactions are controlled with visible light using an optogenetic approach by expressing the blue light switchable proteins CRY2 or CIBN on the surfaces of cells. CRY2 and CIBN expressing cells form specific heterophilic interactions under blue light providing precise control in space and time. Further, these interactions are reversible in the dark and can be repeatedly and dynamically switched on and off. Unlike previous approaches, these genetically encoded proteins allow for long‐term expression of the interaction domains and respond to nontoxic low intensity blue light. In addition, these interactions are suitable to assemble cells into 3D multicellular architectures. Overall, this approach captures the dynamic and reversible nature of cell–cell interactions and controls them noninvasively and sustainably both in space and time. This provides a new way of studying cell–cell interactions and assembling cellular building blocks into tissues with unmatched flexibility. Abstract : Under blue light illumination, the two cell types, which are expressing either CRY2 or CIBN on their surfaces, interact with each other and dissociate reversibly in the dark. This provides dynamic, reversible, and high spatiotemporal control over cell–cell interactions in a noninvasive and sustainable manner for applications in bottom‐up tissue engineering and cell biology.